FUTURE PROSPECT FOR BUFFALO DEVELOPMENT IN WEST SULAWESI PROVINCE BASED ON REPRODUCTIVE MANAGEMENT APPLIED - Yusuf, Muhammad; Baco, Sudirman; Karim, M. Nasir (Proceeding Buffalo International Conference, 2013)
The objective of this study was to know the application of reproductive management of buffalo in West Sulawesi Province and its potential for development in the future. This study was conducted during a period from July to August 2012 in three different sub-districts; Mehalaan, Messawa, and Nosu. Primary data was collected with the help of a questionnaire to the 60 farmers that included the number of buffalo, raising management, and reproductive management. While secondary data was obtained from related institution such as local government and livestock service. The results of this study showed that reproductive management applied by the farmers was still very low. Mating system of buffaloes in this area was two different methods; natural mating without any help and natural mating with the help of the farmers. Mostly farmers had good knowledge about estrus. Most of them were capable to identify buffaloes in estrus by observing their behavior. In order to improve buffalo development in this region, it is necessary to involve short- and long terms such as extension to the farmers, recording, dietary management, manipulation of the estrous cycle and control of ovulation, the use of high fertility buffalo bulls (natural mating) and AI, crossbreeding, genetic selection, and sustainable management improvement. Therefore, it is potential for future buffalo development in this area such as improvement the general knowledge of the farmers in raising buffalo and enhances the reproductive management in order to increase pregnancy rate and calving rate, and reduces mortality rate.